Determinants of food safety practices among food handlers in selected food establishments - Abdu Oumer (Intelektual Pustaka Media Utama, 2019)
Despite great efforts against foodborne diseases, the occurrence of these problems remains a significant health issue in both developed and developing countries. This study was to assess determinants of food safety practice among food handlers in selected food establishments in Dire Dawa City administration, in 2017. Cross sectional survey was conducted among 356 food handlers from the selected food establishments in different categories. The CODEX food safety questionnaire was used to assess food safety knowledge (23 questions), attitude (six questions) and practice using interview and observation checklists (15 points). Satisfactory practice was defined as those who practice 70% of food safety measures correctly. Frequency, percentage, mean, binary logistic regression with a crude odds ratio and adjusted odds ratio (AOR) at 95% confidence interval were calculated. Out of the total study subjects, 354 food handlers participated in this study with 99.4% response rate. A total of 191 food handlers, 54.0% were female with overall mean age of 29.5 years. About 129 (36.4%), 194 (54.8%) and 106 (29.9%) had adequate knowledge, positive attitude and satisfactory food safety practice. Having food safety training (AOR= 2.0), with adequate knowledge (AOR = 2.83), positive attitude (AOR= 2.09), presence of food safety guideline (AOR = 2.23) and supervision (AOR= 2.07) were significant predictors of satisfactory food safety practices. In general food safety/hygienic practices of food handlers was found to be low. Having adequate knowledge, positive attitude, presence of food safety guideline and formal food safety training were significant predictors of food safety practices among food handlers.